2023
DOI: 10.1186/s12868-023-00800-9
|View full text |Cite
|
Sign up to set email alerts
|

The glycine receptor alpha 3 subunit mRNA expression shows sex-dependent differences in the adult mouse brain

Abstract: Background The glycinergic system plays an important inhibitory role in the mouse central nervous system, where glycine controls the excitability of spinal itch- and pain-mediating neurons. Impairments of the glycine receptors can cause motor and sensory deficits. Glycine exerts inhibition through interaction with ligand-gated ion channels composed of alpha and beta subunits. We have investigated the mRNA expression of the glycine receptor alpha 3 (Glra3) subunit in the nervous system as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(83 reference statements)
2
2
0
Order By: Relevance
“…The latter study is more consistent with our observations as the Glra3 -Cre(+) populations were localized in both the dorsal and ventral laminae ( Fig. 1 A–C ), which is also in agreement with mRNA expression of Glra3 ( Ceder et al, 2023 ). To investigate the dendritic localization of Glra3 -Cre(+) neurons, we performed cell fillings ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The latter study is more consistent with our observations as the Glra3 -Cre(+) populations were localized in both the dorsal and ventral laminae ( Fig. 1 A–C ), which is also in agreement with mRNA expression of Glra3 ( Ceder et al, 2023 ). To investigate the dendritic localization of Glra3 -Cre(+) neurons, we performed cell fillings ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, starter, lineage, and virally labeled Glra3 -Cre(+) cells were observed in the ventral horn. In line with these observations, we recently showed that Glra3 is detected in the dorsal and ventral horns of the lumbar division ( Ceder et al, 2023 ). Thus, it remains unclear whether sensory-mediating Glra3 -Cre(+) neurons receive motor input or if the ventrally located Glra3 -Cre population have motor functions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Conversely, agonist binding to inhibitory channels GlyR and GABA A R induces an inward flow of chloride anions into the cell, provoking membrane potential hyperpolarization and decreased cellular excitability . While the expression patterns of GlyRs and GABA A Rs exhibit some overlap and emerging evidence suggests that GlyRs are ubiquitously expressed in several areas in the central nervous system (CNS), GABA A Rs are generally described as the primary mediators of inhibitory signals within the brain, whereas GlyRs would act predominantly in the spinal cord and brainstem, regulating a variety of motor and sensory functions . Their regulatory role in the CNS combined with the structural diversity of their modulators (several of which, including benzodiazepines, neurosteroids, cannabinoids, and volatile anesthetics, are currently used to treat psychiatric and neurological disorders such as anxiety, schizophrenia, epilepsy, and chronic pain) make these receptors highly exploitable targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%